2023
DOI: 10.3390/coatings13091652
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Strength Formation Mechanism and Water Stability of Geopolymer Stabilized Phosphogypsum in Road Construction

Yi Wu,
Hanbin Zhang,
Haikun Lin
et al.

Abstract: By adjusting the content of geopolymer in geopolymer stabilized phosphogypsum (GSP) as roadbed filler, along with the mixing ratio, this paper mainly explores tendencies in the mechanical properties and water stability of GSP. This research is based on macro-mechanical properties such as unconfined compressive strength, resilience modulus, California bearing ratio and shear strength. It is also based on water stability tests, such as the water soaking test, dry and wet cycle test and expansion test, to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Through on-site CBR testing, it was found that both met the relevant requirements. Wu [20] used cementitious materials to solidify phosphogypsum to form full solid waste materials for roadbed filling. In summary, solid waste-based cementitious materials can meet performance requirements in the solidification of heavy metals and as cementitious materials for concrete, road base, and roadbed solidification, and they exhibit some superior properties compared to traditional measures, such as the solidification of heavy metal cadmium, the freeze-thaw resistance of road base materials, and sulfate corrosion resistance in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Through on-site CBR testing, it was found that both met the relevant requirements. Wu [20] used cementitious materials to solidify phosphogypsum to form full solid waste materials for roadbed filling. In summary, solid waste-based cementitious materials can meet performance requirements in the solidification of heavy metals and as cementitious materials for concrete, road base, and roadbed solidification, and they exhibit some superior properties compared to traditional measures, such as the solidification of heavy metal cadmium, the freeze-thaw resistance of road base materials, and sulfate corrosion resistance in concrete.…”
Section: Introductionmentioning
confidence: 99%